2002
DOI: 10.1097/00006231-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inflammatory bowel disease by using two different 99mTc leucocyte labelling methods

Abstract: The aim of this study was to retrospectively compare the diagnostic accuracy of (99m)Tc hexamethylpropyleneamine oxime (HMPAO) white blood cell scintigraphy in patients with a suspicion of active inflammatory bowel disease by using two different cell suspension media: leukocyte poor plasma (LPP) and Hanks' balanced salt solution (HBSS). Leukocytes from 30 patients were labelled using LPP and in 28 cases using HBSS. In the LPP method the leukocytes were resuspended in 0.5 ml cell-free plasma while in the HBSS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…On the other hand, the labeling yield for leukocytes was 55.0% ± 10%. Labeling yields of 46% and 65.5% have been reported previously [19,20] . Thus, the value obtained in the present work is supported by published data, which suggests that the manipulation process utilized in the preparation of the radiolabeled cells was adequate.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the labeling yield for leukocytes was 55.0% ± 10%. Labeling yields of 46% and 65.5% have been reported previously [19,20] . Thus, the value obtained in the present work is supported by published data, which suggests that the manipulation process utilized in the preparation of the radiolabeled cells was adequate.…”
Section: Discussionsupporting
confidence: 52%
“…Radiolabeled leukocytes in the Crohn's disease diagnostic screening of inflammatory diseases [4] . Cardoso et al [19] have observed sensitivity, specificity and accuracy values of > 87.5% in studies performed in patients highly suspected of having inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…To label the leukocyte, it is necessary to take blood from the patient, its leukocyte be separated, then labeled, and finally reinjected to the patient. This technique is time consuming, and the potential of contamination or transmission of blood‐borne pathogens to patient or technician is high . 67 Ga‐citrate is the most initial radionuclide for this propose, but unfortunately, it has several disadvantages such as long physical half‐life; high and multiple energy gamma ionizing radiation, which causes high radiation absorbed doses; lack of availability as a generator; and high sensitivity for both infection and sterile inflammation .…”
Section: Introductionmentioning
confidence: 99%